Ecologia trófica do polvo Octopus insularis (Cephalopoda: Octopodidae): comparações metodológicas e nova perspectiva através do uso de isótopos estáveis de carbono e nitrogênio - Dantas, Renato Junqueira de Souza (2017)
Octopuses are the most important cephalopods in the benthic environment, since they act as generalist and opportunistic predators, consuming a wide variety of organisms. Their trophic ecology has already been studied using several methodologies applied to a variety of species in different locations. However, there is no consensus on which technique would be more effective in this type of research, or even if the use of only one method would be sufficient. Therefore, the objective of this study was to compare three different qualitative and quantitative methods (analysis of midden piles, digestive content and stable isotopes) to characterize the diet of Octopus insularis, the most frequent octopus on the northeast coast of Brazil and its oceanic islands. The study areas were: the Biological Reserve of Rocas Atoll, an insular, pristine and unique environment in Southern Hemisphere; and Rio do Fogo, inside the State Marine Protected Area of Coral Reefs, a coastal environment, with human occupation and fishing impact. In Rocas Atoll, the three methods were used and showed different results. Although midden piles and digestive content have pointed crustaceans as the main prey, only the material found in the stomachs showed that fishes and polychaetes occurred in the diet and in considerable amounts. Both showed similar proportions of mollusks in the diet, but differed in the type of such organisms (gastropods in the dens and cephalopods in the stomachs). The isotopes pointed mollusks as main prey and crustaceans as secondary prey, corroborated the contributions of fish and polychaetes exhibited by the digestive content and showed that echinoderms are also part of the diet. In Rio do Fogo, only the dens and the stomach contents were evaluated, so that the first one pointed to bivalves as major prey and crustacean in minimal quantities, and the second highlighted crustaceans as the most consumed prey, accompanied by small amounts of mollusks (gastropods, bivalves and chitons), fishes and polychaetes. In general, midden piles show remains of hard and heavy structures of prey, such as shells and carapaces, and underestimate those with high proportions of soft tissues, which are found in the stomachs. The isotopes, on the other hand, show the prey with higher rates of assimilation and may be influenced by their energy content. In addition, abiotic (waves and currents) and biotics factors (rapid digestion of octopuses and other animals feeding in the dens) may also alter the results. Finally, it is suggested the use of at least two complementary methods, depending on the research goals, the species and area to be studied.